URGENSI REKONSTRUKSI HUKUM TERKAIT PERLINDUNGAN DATA DI INDONESIA - FAYZA KHAIRUNNISA MOODOETO (Universitas Mahasaraswati K. Mataram, 2024)
Every activity is always based on the law, especially the law on Information and Electronic Transactions and the law on personal data protection, which is considered urgent in the current era of digital transformation. The law must be able to oversee community activities, because daily activities are inseparable from technology. If users are not equipped with data security systems and experience, there is a concern that they will be vulnerable to cybercrime. Law Number 11 of 2008 concerning Information and Electronic Transactions and Law Number 27 of 2022 concerning Personal Data Protection, which regulate cybercrime in general but have not yet been comprehensively addressed, cause concern among the public.This research is structured with a normative type through a conceptual and legislative approach, as well as through a case approach by analyzing cases related to cybercrime, such as the recent data breach involving President Joko Widodo. Based on these conditions, it is very urgent to enforce cybercrime law and reconstruct laws related to cybercrime in the Digital Transformation Era, similar to countries that already have specific regulations like the General Data Protection Regulation (GDPR). The enforcement of the law can start with the implementation of Law Number 11 of 2008 concerning Electronic Information and Transactions and Law Number 27 of 2022 concerning Personal Data Protection, and then reconstruct the laws related to cybercrime to produce regulations that comprehensively address cybercrime. The hope is that this method can address the challenges of society in the era of digital transformation.